Eksplorasi Etnomatematika Pada Kain Tenun Songke Manggarai Dan Integrasinya Dalam Pembelajaran Matematika - Hepy, Timoteus Windy; Dominikus, Wara Sabon; Madu, Aleksius (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2025)
The connection between mathematics and culture is a strong foundation for enriching the mathematics learning process. Therefore, it is hoped that school mathematics learning activities can be better adapted to the cultural context of students so that mathematics can be more easily understood by students. One cultural context that can be used is the ethnomathematics of Songke Manggarai woven cloth. The type of research used in this research is qualitative research with a qualitative descriptive research method with an ethnographic approach. In this research, the instruments used were interviews and observations. Data collection techniques in this research consist of observation, interviews and documentation. The data analysis technique used in this research is the interactive model from Miles & Huberman (1994), which states that the data collection stage consists of three activities that occur simultaneously, namely data reduction, data presentation, and conclusion drawing/verification. Based on the results of this ethnomathematics exploration research, it can be concluded that there are mathematical concepts in the Songke Manggarai woven cloth of Golo Ronggot Village, both in the initial process and in the stages of the weaving process.